Aggressive angiomyxoma of pelvic parts exhibits oestrogen and progesterone receptor positivity. Issue 8 (1st August 2000) - McCluggage, W G; Patterson, A; Maxwell, P
Abstract : Aims —Aggressive angiomyxoma of pelvic parts is a distinctive soft tissue tumour that chiefly involves the vulvar and perineal region of female patients. Several previous reports have demonstrated oestrogen receptor (ER) and/or progesterone receptor (PR) positivity in this neoplasm. The aim of this study was to confirm whether ER and/or PR positivity is present in aggressive angiomyxoma. We also wished to ascertain whether positivity may be found in the stromal cells of normal vulval skin and in other lesions at this site that can cause diagnostic confusion with aggressive angiomyxoma. Methods —Five aggressive angiomyxomas in female patients and one involving male pelvic soft parts were stained immunohistochemically with antibodies against ER and PR. Other samples studied were normal vulval skin (n = 7), fibroepithelial polyps of vulva (n = 7), vulval smooth muscle neoplasms (n = 5), vulval nerve sheath tumours (n = 2), vaginal angiomyofibroblastoma (n = 1), and pelvic myxoma (n = 1). Nuclear staining was classified as negative, weak, moderate, or strong and the proportion of positively staining cells was categorised as 0, < 10%, 10–50%, or > 50%. Results —All five cases of aggressive angiomyxoma in female patients were positive for ER (two with weak intensity involving < 10% of cells and three with moderate intensity involving 10–50% of cells) and four of five cases were strongly positive for PR in > 50% of cells. The other case was negative for PR. There was no staining with antibodies to ER or PR in the single male patient with aggressive angiomyxoma. Other samples exhibiting positivity of the stromal cells for either ER or PR were normal vulval skin (five of seven, ER; two of seven, PR), fibroepithelial polyps (four of seven, ER; five of seven, PR), smooth muscle neoplasms (three of five, ER; four of five, PR), nerve sheath tumours (one of two, ER; one of two, PR), angiomyofibroblastoma (one of one, ER; one of one, PR), and pelvic myxoma (one of one, PR). Conclusions —All cases of aggressive angiomyxoma of pelvic soft parts in female patients exhibited positivity for ER and/or PR. Because of its propensity to occur in female patients during the reproductive years, it is possible that aggressive angiomyxoma is a hormonally responsive neoplasm. However, dermal fibroblasts in normal vulval skin and stromal cells in a variety of vulval lesions can also be positive. ER or PR immunoreactivity cannot be used to distinguish aggressive angiomyxoma and its histological mimics.